KETERLIBATAN PETANI KOPI PEREMPUAN DALAM MENUNJANG KEBERLANJUTAN PERTANIAN KOPI DI DESA RIGIS JAYA KABUPATEN LAMPUNG BARAT - Muhammad Syah Fadhel; Dadang Karya Bakti; Winda Saptiani (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research explains the involvement of women coffee farmers in supporting the sustainability of coffee farming in Rigis Jaya Village, West Lampung Regency. The research method used was qualitative with data collection techniques through in-depth interviews with female coffee farmers in Rigis Jaya Village. The results showed that women coffee farmers are involved in supporting the sustainability of coffee farming, this can be seen in the marketing sector, ecological, economic and social sectors. In terms of marketing, women farmers are involved in selling the harvest of coffee cultivation to coffee collectors. this is shown by women farmers participating in packaging coffee beans that will be submitted to collectors. Furthermore, based on observation, Rigis Jaya coffee has social media and a website to market coffee to customers. Involvement in the ecological sector, namely in terms of fertilisation with organic fertiliser, pest control by spraying and maintaining coffee plants, weed control, and picking. Involvement in the economic sector, namely in helping family income by being involved in coffee cultivation, fruit and vegetable cultivation, goat and cow farming, and there are female farmers who also work as village clerks to support the family economy. Involvement in the social sector, women coffee farmers join the Women Farmers Group (KWT) which meets every month, by being active in the Women Farmers Group (KWT) is able to get training in managing coffee farming. This research has important implications for local governments and related stakeholders to develop programmes and policies that support the development of women farmers. Agricultural counselling and financial funding can assist women farmers in supporting the sustainability of coffee farming.